2012
DOI: 10.1111/j.1365-2761.2012.01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of bacterial probiotic candidates from the gastrointestinal tract of rainbow trout, Oncorhynchus mykiss (Walbaum), and screening for inhibitory activity against Flavobacterium psychrophilum

Abstract: In this study, 318 bacterial strains were isolated from the gastrointestinal (GI) tracts of 29 rainbow trout, Oncorhynchus mykiss (Walbaum). These bacteria were screened in vitro for their ability to inhibit growth of Flavobacterium psychrophilum, the causative agent of coldwater disease. Bacteria observed to inhibit F. psychrophilum growth were further screened against rainbow trout bile, as an indicator of their ability to survive in the GI tract. This screening resulted in narrowing the pool to 24 bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Thus, tolerance to the bile juice represented by the gut isolates in the present study was relatively high. Similar observations were recorded by several authors to establish bile tolerance of the putative probiotic bacteria against fi sh bile (Nikoskelainen et al 2001, Burbank et al 2012, Mukherjee and Ghosh 2014 or commercial bile salts (Allameh et al 2014, Geraylou et al 2014). Finally, bio-safety towards the host is an indispensable criterion for any of the probiotic bacteria under critical evaluation (Verschuere et al 2000).…”
Section: Discussionsupporting
confidence: 67%
“…Thus, tolerance to the bile juice represented by the gut isolates in the present study was relatively high. Similar observations were recorded by several authors to establish bile tolerance of the putative probiotic bacteria against fi sh bile (Nikoskelainen et al 2001, Burbank et al 2012, Mukherjee and Ghosh 2014 or commercial bile salts (Allameh et al 2014, Geraylou et al 2014). Finally, bio-safety towards the host is an indispensable criterion for any of the probiotic bacteria under critical evaluation (Verschuere et al 2000).…”
Section: Discussionsupporting
confidence: 67%
“…In brief, bacteria were isolated from the GIT of healthy individuals of wild (North Atlantic) and farmed turbot (Stolt Sea Farm AS, Øyestranda, Norway). Bacterial isolates were identified by sequencing the partial 16S rRNA gene using universal eubacteria primers EUB 1F: 5’ AATTGAAGAGTTTGATCATGGCTCA 3’ and EUB 907R: 5’ CCGTCAATTCCTTTRAGTTT 3’ (Burbank, LaPatra, Fornshell, & Cain, ) and BLAST analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Burbank et al (23) first showed that Enterobacter C6-6 culture or spent medium inhibited growth of F. psychrophilum in a manner consistent with the presence of a soluble inhibitor. Herein we successfully identified a small protein (entericidin B) in the supernatant of Enterobacter C6-6 cultures that is linked to the inhibitory phenotype in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…strain C6-6, was recently isolated from trout intestines and was shown to inhibit F. psychrophilum on agar diffusion plates (23) while reducing mortality during F. psychrophilum challenge studies (24). The agar diffusion data indicated that the cell-free supernatant of this probiotic strain could inhibit F. psychrophilum growth in vitro.…”
mentioning
confidence: 99%